2010
DOI: 10.1124/jpet.109.163949
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine Up-Regulates Krüppel-Like Factor-4 (KLF4) in Vascular Smooth Muscle Cells and Drives Phenotypic Modulation In Vivo

Abstract: Cyclosporine A (CSA, calcineurin inhibitor) has been shown to block both vascular smooth muscle cell (VSMC) proliferation in cell culture and vessel neointimal formation following injury in vivo. The purpose of this study was to determine molecular and pathological effects of CSA on VSMCs. Using real-time reverse transcription-polymerase chain reaction, Western blot analysis, and immunofluorescence microscopy, we show that CSA upregulated the expression of Krü ppel-like factor-4 (KLF4) in VSMCs. KLF4 plays a k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 47 publications
0
29
0
Order By: Relevance
“…Cyclosporine, which induces KLF-4 expression, also induces smooth muscle cell dedifferentiation (37). In contrast, myocardin overexpression promotes VSMC differentiation and increases the expression of other VSMC marker proteins (38).…”
Section: Irs-1 Prevents Vsmc Dedifferentiationmentioning
confidence: 99%
“…Cyclosporine, which induces KLF-4 expression, also induces smooth muscle cell dedifferentiation (37). In contrast, myocardin overexpression promotes VSMC differentiation and increases the expression of other VSMC marker proteins (38).…”
Section: Irs-1 Prevents Vsmc Dedifferentiationmentioning
confidence: 99%
“…Further, miR-145 represses Kruppel-like factor 4 (Klf4), which was shown to be involved in multiple events including neointimal proliferation. Klf4 plays a key role in regulating the VSMC phenotype because it facilitates VSMC migration and downregulates VSMC differentiation marker genes (9).…”
Section: Introductionmentioning
confidence: 99%
“…43 Klf4 plays a key role in regulating VSMC phenotype because it antagonizes proliferation, facilitates migration, and downregulates VSMC differentiation marker genes. 44 In another study, versican was identified as a new target for miR-143. 45 Versican is a chondroitin sulfate proteoglycan of the extracellular matrix, produced by synthetic VSMCs, and promotes VSMC migration and proliferation.…”
Section: Mir-143/145 Regulation Of Vsmc Proliferation and Differentiamentioning
confidence: 99%